Islamic Character Education Through "Ngajeni" Culture - Rofi'ah, Siti Hamidahtur; Ansori, Muhammad; Puspitasari, Nita (Proceedings of Annual Conference for Muslim Scholars, 2025)
Bullying is a global problem that impacts students' psychological development and character. In Indonesian education, integrating local wisdom and Islamic values ​​is a crucial strategy for preventing bullying. One prominent practice is the Ngajeni culture in Yogyakarta, which teaches manners, respect, and politeness in accordance with Islamic values ​​of noble morals and rahmatan lil 'alamin (blessing for the universe). The study used a qualitative method with a case study design at Patalan Baru Elementary School, Bantul, Yogyakarta. Data were collected through observation, interviews, and documentation. The results showed that Ngajeni culture was implemented through three main strategies: polite verbal expressions (greetings, thanks, apologies), symbolic gestures (ngapurancang) as a sign of respect, and the inculcation of Islamic morals in school life. These practices foster empathy, brotherhood, and respect for differences. The findings confirm that the integration of Ngajeni culture and Islamic values ​​not only preserves the culture but also serves as a framework for local wisdom for bullying prevention and strengthening character education in elementary schools.